2001
DOI: 10.1046/j.1365-2222.2001.00995.x
|View full text |Cite
|
Sign up to set email alerts
|

IL‐5 priming of the PMA‐induced oxidative metabolism of human eosinophils from allergic and normal subjects during a pollen season

Abstract: Blood eosinophils from allergic patients are primed in vivo, as compared to eosinophils from non-allergic controls, during a pollen season. Interleukin-5 primes equally the PMA-induced oxidative metabolism of human eosinophils from healthy or allergic subjects. The mechanism of IL-5 priming after PMA stimulation of oxygen radical production is MEK independent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The function of human eosinophils is largely regulated by IL-5 family cytokines, including IL-5, IL-3 and GM-CSF (7–10). Recently, several lines of evidence demonstrate that IL-5 family members can enhance blood eosinophil responsiveness to a second stimulus, such as the chemotactic factors CCL5 and formyl-Met-Leu-Phe (fMLP), resulting in a synergistic response known as “priming” (1015). The capacity of IL-5 family cytokines to prime blood eosinophils for altered chemoattractant responsiveness has been associated with changes in intracellular signaling events, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of human eosinophils is largely regulated by IL-5 family cytokines, including IL-5, IL-3 and GM-CSF (7–10). Recently, several lines of evidence demonstrate that IL-5 family members can enhance blood eosinophil responsiveness to a second stimulus, such as the chemotactic factors CCL5 and formyl-Met-Leu-Phe (fMLP), resulting in a synergistic response known as “priming” (1015). The capacity of IL-5 family cytokines to prime blood eosinophils for altered chemoattractant responsiveness has been associated with changes in intracellular signaling events, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of IL-5 family cytokines to prime blood eosinophils for altered chemoattractant responsiveness has been associated with changes in intracellular signaling events, e.g. an increase in chemoattractant-induced phosphorylation of the mitogen-activated protein kinases ERK1 and 2 (11), and biological responses, such as chemotaxis, degranulation and the release of proinflammatory mediators (7, 9, 10, 12, 14, 15). Furthermore, the priming of blood eosinophils with IL-5 family members allows for these cells to exhibit a similar phenotype and hyper-responsiveness as that observed with airway eosinophils (9, 16–19).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, eosinophils purified from symptomatic asthmatics generate higher ROS on activation of plateletactivating factor or phorbol myristate acetate than those of asymptomatic asthmatics [16]. This study demonstrated that ketotifen inhibited the production of ROS from eotaxin-primed human eosinophils at concentrations of 10 -10 -10 -6 mol/l.…”
Section: Discussionmentioning
confidence: 67%
“…Gö 6983 was found to strongly inhibit superoxide anion release from eosinophils isolated from human patients allergic to birch pollen (77). This finding suggests that Gö 6983 may be effective in inhibiting symptoms associated with rhinitis or asthma.…”
Section: Clinical Studies With Gö 6983 and Other Pkc Inhibitorsmentioning
confidence: 82%
“…Gö 6983 represents a potentially useful therapeutic tool in settings of exaggerated immune responses (i.e., allergic) to attenuate leukocyte activity. Gö 6983 was found to strongly inhibit superoxide anion release from eosinophils isolated from human patients allergic to birch pollen (77). This finding suggests that Gö 6983 may be effective in inhibiting symptoms associated with rhinitis or asthma.…”
Section: Clinical Studies With Gö 6983 and Other Pkc Inhibitorsmentioning
confidence: 82%